2001
DOI: 10.1046/j.1464-5491.2001.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of pregnancy outcome in pregestational diabetes through functional insulin treatment and modular out‐patient education adapted for pregnancy

Abstract: Structured, comprehensive, modular out-patient group education promoting self-choice of insulin dose for flexible, normal eating prior to conception normalizes pregnancy outcome in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 35 publications
1
16
0
2
Order By: Relevance
“…The fact that in our study metabolic control in the first trimester was significantly better in T2DM than in T1DM patients is consistent with many previous reports [23][24][25][26][27][28][29][30][31]. The improvement in glycemic control in subsequent trimesters is an obvious result of the treatment intensification during the pregnancy [32]. Interestingly, mean HbA1c in T2DM and T1DM subjects in the second and third trimesters was within the goal of glycemic control as set by international and local guidelines [19,[33][34][35][36].…”
Section: Discussionsupporting
confidence: 94%
“…The fact that in our study metabolic control in the first trimester was significantly better in T2DM than in T1DM patients is consistent with many previous reports [23][24][25][26][27][28][29][30][31]. The improvement in glycemic control in subsequent trimesters is an obvious result of the treatment intensification during the pregnancy [32]. Interestingly, mean HbA1c in T2DM and T1DM subjects in the second and third trimesters was within the goal of glycemic control as set by international and local guidelines [19,[33][34][35][36].…”
Section: Discussionsupporting
confidence: 94%
“…SUs have been shown to be more effective than insulin for glycemic diabetes control in PNDM related to Kir6.2 in patients of various ages (4,7,9,10). The normalization of glucose levels is a priority to improve the maternal and neonatal outcomes of pregnancies complicated by diabetes (17). Hyperglycemia during organogenesis is associated with increased risk of congenital malformations affecting the neural tube, heart, and skeleton (18).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal hypoglycemia occurred mainly within 3 h of birth and all in preterm deliveries, a well-known risk factor for this neonatal complication 32 ; moreover, the frequency of neonatal hypoglycemia recorded in the present study (17%) was comparable to that reported in other European studies. 20,33,34 We also recorded a low percentage of cumulative respiratory disorders in neonates. This last finding allowed the return to the ward and breastfeeding in the majority of newborns as demonstrated by the low percentage of neonatal intensive care unit admissions.…”
Section: Discussionmentioning
confidence: 99%